Respostas

A melhor resposta!
2014-05-05T17:50:56-03:00
a) 5x-6=2x+3

5x-2x-6-3=0
3x-9=0
3x=9
x=9/3
x=3

b) 
7(x+2)=2x-6

7x+14-2x+6=0
5x+20=0
5x= -20
x= -20/5
x -4

2 5 2
obrigado.. me ajudou bastante :)
  • Usuário do Brainly
2014-05-05T18:28:58-03:00
A) 5x-6=2x+3
b)7(x+2)=2x-6


resolvendo letra a.
                              a) 5x - 6 = 2x + 3
                                 5x -2x = 3 +6
                                  3x= 9
                                    x = 9/3
                                     x = 3
resolvendo letra b.
                             b) 7 ( x + 2 ) = 2x - 6
                                 7x + 14 = 2x - 6
                                   7x - 2x = -6 -14
                                         5x = -20
                                           x = -20/ 5
                                           x = - 4
1 5 1